Specifying Clauses in the Administrative-Legal Style of 19th-Century Serbian Language - Pavlović Jovanović, Jelena M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper examines the status of specifying clauses in the administrative-legal style of the Serbian language dating back to the 19th century. The corpus includes texts from 19th-century constitutions (adopted in 1835, 1838, 1869, 1888, and 1901) and the Collection of Laws and Decrees adopted by the Principality/Kingdom of Serbia. To isolate the normative-legal and ideological layers of the texts, the analysis employs a combination of historical-linguistic, syntactic-semantic, and functional methods, as well as legal theory methodology. As a result of the recent development of the Serbian language, the specifying meaning is only found infrequently in the examined corpus. Clauses introduced by the conjunction с тим да occur in postpositions and encode information of secondary importance to administrative-legal norms. Furthermore, an online (available) search of the Legal Information System of the Republic of Serbia reveals that the specifying meaning is only marginal even in modern legal language.
Keywords: administrative-legal style; Serbian language; 19th century; specifying clauses